Web Service Composition for E-Commerce Web Application - ISMAIL, Anis; AL HAJJAR, Abd El Salam; KASSEM, Abdel Karim (Review of Computer Engineering Research, 2016)
Web Services are based on distributed technology and provide standard means of interoperating between different software applications across and within organizational boundaries with the use of XML. Web Services technologies allow interaction between applications. Sometimes a single service given alone does not meet user’s needs. In this case, it is necessary to compose several services in order to achieve the user’s goal. Web service composition is one of the most challenging problems of recent years. The number of service providers is increasing, and along with that for a request they offer multiple services with the same functionality, so it makes the problem of composition quite complex. In this paper, we compose multi web services for E-Commerce. We implement a new web application that use two or many web services to make some transactions and to choose the best deal.